Improving clinical outcomes via responsible antimicrobial use in horses. (3rd June 2021) - Isgren, C. M.
Summary: The growing problem of antimicrobial resistance affects veterinarians on a daily basis. Antimicrobial stewardship and responsible prescribing are essential for a future with effective antimicrobials, as it is unlikely that new antimicrobials will become available for use in horses in the near future. Extended‐spectrum β‐lactamase (ESBL) producing Enterobacteriaceae, methicillin‐resistant Staphylococcus aureus (MRSA) and Salmonella spp. are pathogens of significant concern but there are also other opportunistic pathogens such as Pseudomonas spp., α‐haemolytic Streptococcu s spp., Enterococcus spp. and Acinetobacter spp. which, due to their high intrinsic resistance, have limited treatment options in adult horses. It is essential that highest priority critically important antimicrobials such as ceftiofur, enrofloxacin, rifampicin and polymyxin B are used prudently in horses and ideally based on culture and antimicrobial susceptibility testing (AST). For example, the use of polymyxin B at a low anti‐endotoxic dose rather than at a higher antimicrobial dose in horses for the treatment of systemic inflammatory response syndrome is a potential driver for resistance to colistin (polymyxin E), an antimicrobial used as a last resort in the treatment of multidrug resistant (MDR) Enterobacteriaceae infections in humans. Serum procalcitonin levels are used in humans to distinguish noninfectious inflammatory conditions from inflammation caused by bacteria and other infectious agents and are also used to guide cessation of antimicrobial treatment. Although no such studies have been performed in horses, this or other markers may prove to be helpful in guiding antimicrobial treatment decisions in the future. Optimising sampling techniques and good communication with the microbiology laboratory are essential for generating the accurate culture and AST results that underpin appropriate antimicrobial use. Additionally, there is clearly a need for national and international harmonisation of laboratory methods in order to improve the reliability and consistency of results reported by different laboratories.